Synthesis, structural and photophysical properties of dimethylphosphino(perfluoro-)phenylene-based gold(i) dimers. Issue 5 (13th January 2022) - Müller, Felix; Wickemeyer, Lucas; Schwabedissen, Jan; Ertl, Martin; Neumann, Beate; Stammler, Hans-Georg; Monkowius, Uwe; Mitzel, Norbert W.
Abstract : Driven by different weak non-covalent interactions [Au2 (μ2 -C6 H4 PMe2 )2 ] and its aryl-perfluorinated analogue aggregate vastly differently in the solid state: the non-fluorinated prefers aurophilic interactions, the fluorinated aryl–aryl interactions. Abstract : Starting with 1, 2-dibromobenzene and 1, 2, 3, 4-tetrafluorobenzene, dimethyl(2-(trimethylstannyl)phenyl)phosphane, Me2 P( o -C6 H4 )SnMe3, and dimethyl-[2, 3, 4, 5-tetrafluoro-6-(trimethylstannyl)phenyl]phosphane, Me2 P( o -C6 F4 )SnMe3, were synthesized and used in tin-gold exchange reactions to prepare two gold(i ) dimers, bis[(2-dimethylphosphino)phenyl]di-gold(i ), [Au2 (μ-2-C6 H4 PMe2 )2 ], and bis[(2-dimethylphosphino)-3, 4, 5, 6-tetrafluorophenyl]di-gold(i ), [Au2 (μ-2-C6 F4 PMe2 )2 ], respectively. Both tin precursor molecules, as well as the gold(i ) complexes, were characterized by multinuclear NMR spectroscopy, CHN analysis and X-ray diffraction experiments. Both gold(i ) dimers were further investigated by the means of computational as well as photophysical methods.